Alokace expozitur ve veřejné správě - Jelínková, Jana (Univerzita Pardubice, 2007)
The contribution deals with optimal distribution of Register Offices in particular registration distriets of Pardubice region. Various algorithms (e.g. belonging to theory of graphs or linear programming) can be applied to solve this problem. This issue was solved by Floyd's algorithm on the basic of the theory of graphs.

The contribution deals with optimal distribution of Register Offices in particular registration distriets of Pardubice region. Various algorithms (e.g. belonging to theory of graphs or linear programming) can be applied to solve this problem. This issue was solved by Floyd's algorithm on the basic of the theory of graphs.
Keywords: reforma veřejné správy; veřejnosprávní orgány; alokace; správní obvody; Floydův algoritmus